The aspect of physiological idiomatic expressions in everyday English language - Коляда, Ірина Валеріївна; Суханова, Тетяна Євгенівна (Університет Григорія Сковороди в Переяславі, 2024)
The lexical composition of the English language contains a large number of idioms corresponding to the certain age and people’s physiology. Idioms are evolving, and they may change and get out of use from time to time. Speaking of a foreign language as a native one is, first of all, the ability to easily and naturally communicate on any topic with its native speakers, regardless of their gender, age, cultural and other individual characteristics. This is the same lively conversational speech that you hear in shops, cafes and clubs, in public transport and outside when travelling abroad. A significant part of it is an idiom, which we are to talk about in this article. In our humble opinion, we are to define the term “an idiomatic expression” or “an idiom”. According to the Oxford Dictionary “idiomatic expressions are a type of informal language that have a meaning different from the meaning of the words in the expression”. We would like to give an example of some idioms in English: “out of the blue”, “to hold the tongue” and “Break a leg”.

Лексичний склад англійської мови містить велику кількість ідіом, що можуть використовуватися коли мова йде про фізіологію людини. Ідіоми розвиваються, і вони можуть час від часу змінюватися та виходити з ужитку. Говорити про іноземну мову як про рідну – це, перш за все, вміння легко і природно спілкуватися на будь-яку тему з її носіями, незалежно від їх статі, віку, культурних та інших індивідуальних особливостей. Це та сама жвава розмовна мова, яку ви чуєте в магазинах, кафе і клубах, в громадському транспорті і на вулиці під час поїздок за кордон. Значну його частину становить ідіома, про яку ми поговоримо в цій статті. На нашу думку, ми повинні визначити термін «ідіоматичний вираз» або «ідіома». Згідно з Оксфордським словником, «ідіоматичні вирази ‒ це тип неформальної мови, значення якого відрізняється від значення слів у виразі». Ми хотіли б навести приклади деяких ідіом в англійській мові: «несподівано», «to hold the tongue» і «Break a leg».
Keywords: idioms; non-literary vocabulary; colloquial words; meaning; speech phenomenon; ідіоми; нелітературна лексика; розмовні слова; значення; мовленнєвий феномен